Development of Molecular Markers for Iron Metabolism Related Genes in Lentil and Their Expression Analysis under Excess Iron Stress - Sen Gupta, Debjyoti; McPhee, Kevin; Kumar, Shiv (Frontiers in Plant Science, 2017)
Multiple genes and transcription factors are involved in the uptake and translocation of iron in plants from soil. The sequence information about iron uptake and translocation related genes is largely unknown in lentil (Lens culinaris Medik.). This study was designed to develop iron metabolism related molecular markers for Ferritin-1, BHLH-1 (Basic helix loop helix), or FER-like transcription factor protein and IRT-1 (Iron related transporter) genes using genome synteny with barrel medic (Medicago truncatula). The second objective of this study was to analyze differential gene expression under excess iron over time (2 h, 8 h, 24 h). Specific molecular markers were developed for iron metabolism related genes (Ferritin-1, BHLH-1, IRT-1) and validated in lentil. Gene specific markers for Ferritin-1 and IRT-1 were used for quantitative PCR (qPCR) studies based on their amplification efficiency. Significant differential expression of Ferritin-1 and IRT-1 was observed under excess iron conditions through qPCR based gene expression analysis. Regulation of iron uptake and translocation in lentil needs further characterization. Greater emphasis should be given to development of conditions simulating field conditions under external iron supply and considering adult plant physiology.